Raining for the Production of Somay and Herbal Beverages at the Agrotechnology Laboratory of the Faculty of Agriculture, Kediri - Nunuk Helilusiatiningsih; Sumarji; Nadhiva Al Indis (PT FORMOSA CENDEKIA GLOBAL, 2023)
Empowerment of students majoring in Agribusiness, Faculty of Agriculture, UNISKA, is a food processing technology practice activity in a food laboratory. Increasing skills in food processing is very important to add insight in doing business. The aim of the training is to improve creative skills to create new innovations to increase economic value and create job vacancies. Methods of activity are socialization, material counseling and discussion, food processing practices, organoleptic tests, physical tests of the products produced. Parameters measured were steamed somay and fried somay, wedang pokak herbal drink. The results of the organoleptic test for wet somay consumers liked 18 panelists, 0 panelists did not like it, and 7 panelists really liked it. Total panelists 25 people. Almost 96% of panelists liked functional drinks with a score of 20 panelists, really liked 4 people, disliked about 1.